Architectural Typology of the Malay Chinatown Facade: Case: Perniagaan Street of Malay Chinese Village Bagansiapiapi, Rokan Hilir, Riau. - Gladies Imanda Utami Rangkuty (Talenta Publisher, 2019)
Chinatown architecture in Bagansiapiapi is a major component of the Chinatown area as an identity with various facades influenced by local Malay culture. The growth and development of cities with economic orientation is often not in line with the understanding to maintain the image of the building, which has an impact on district transformation which can eliminate the existence of Chinatown architecture that currently exists or intersects with the city Commercial center. This can be seen in the changes in facade formation that took place on the Bagansiapiapi Perniagaan street. The typology of facade architecture of the Chinatown building was carried out with the aim of (i)Knowing the character of the facade shape of Chinatown facade, (ii)Getting the dominant formation in each of the facade forming element , so that Chinatown buildings can still be found. The method used is a qualitative method with a descriptive approach, which is directed at describing and interpreting existing conditions. The analysis used by classifying facades on elements of Malay Chinatown architecture includes types of building dimensions, ownership and function modules, which are formed by facade components (roofs, vents, doors, windows, walls, and stilt construction). The findings of this study are the facade of the Chinatown building in Bagansiapiapi on the facade of formation elements that have dominance: 1) Module composition of the core dimensions (a) 1 function of the house floor with wood 2) The shape of the gable, the formation of plain rectangular windows and two long ornaments downward, the formation of the window extends downward by placing a balanced composition right and left, setting a horizontal wall, using a stilt construction. Keyword: Architecture of Chinatown, Facade Elements, Malay Architecture, Typology